2018
DOI: 10.1080/10942912.2018.1454944
|View full text |Cite
|
Sign up to set email alerts
|

Conformation change of trypsin induced by acteoside as studied using multiple spectroscopic and molecular docking methods

Abstract: The interaction of trypsin with acteoside was studied using ultraviolet visible absorption, fluorescence, synchronous fluorescence, circular dichroism techniques, along with molecular docking method. The fluorescence experiments indicated that acteoside quenched the intrinsic fluorescence of trypsin via a combined quenching process (static and dynamic quenching). The binding constant of acteoside to trypsin obtained was 2.50 × 10 5 L mol −1 at 298 K and the number of binding site was about one under the same e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…39 The red shift indicates conformational changes leading to an increase in the hydrophilicity of the protein. 40 The increase in hydrophilicity increased the binding of paracetamol to the protein, which might hinder the release of the drug. From the graphs, it is evident that paracetamol–HSA had a stronger interaction with the tryptophan residue in the binding site.…”
Section: Resultsmentioning
confidence: 99%
“…39 The red shift indicates conformational changes leading to an increase in the hydrophilicity of the protein. 40 The increase in hydrophilicity increased the binding of paracetamol to the protein, which might hinder the release of the drug. From the graphs, it is evident that paracetamol–HSA had a stronger interaction with the tryptophan residue in the binding site.…”
Section: Resultsmentioning
confidence: 99%
“…After counting the cell number in the cell suspension, cells were seeded into μ-Slide VI 0.4 (Ibidi, Gräfelfing, Germany) with thin polymer coverslips at the culture bottom. Note that trypsin is known as a fluorescent protein 26 and may interfere with cellular autofluorescence signals. However, each seeded culture could be contaminated with almost the equal amount of trypsin even after the washing step, we speculated that the effect of trypsin on autofluorescence signals in mycoplasma (−) and mycoplasma (+) cells was negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Four phenylpropanoid glycosides have also been proven to possess inhibitory activity against trypsin; among these, acteoside had the highest, followed by syringalide A 3′-α- l -rhamnopyranoside, lipedoside A-I, and osmanthuside B. A molecular docking study showed that the phenolic hydroxyl group on the A ring had a greater effect on the inhibitory activity than it did that on the B ring, because the A ring was closer to the binding pocket and was able to form more hydrogen bonds with the key residues Ser-217, Ser-190, Gly-219, and Ser-195 …”
Section: Molecular Dockingmentioning
confidence: 99%